Expert consensus on maintenance treatment for metastatic colorectal cancer in China. Issue 1 (14th January 2016) - Xu, Rui‐Hua; Shen, Lin; Li, Jin; Xu, Jian‐Ming; Bi, Feng; Ba, Yi; Bai, Li; Shu, Yong‐Qian; Liu, Tian‐Shu; Li, Yu‐Hong; Bai, Chun‐Mei; Yuan, Xiang‐Lin; et al.
Abstract: The impact of maintenance therapy on progression‐free survival and overall survival as well as quality of life of Chinese patients with metastatic colorectal cancer has long been under discussion. Recently, some phase III clinical trials have revealed that maintenance therapy can significantly prolong the progression‐free survival while maintain an acceptable safety profile. Based on this evidence and common treatment practice in China, we now generated one Expert Consensus on Maintenance Treatment for Metastatic Colorectal Cancer in China to further specify the necessity of maintenance therapy, suitable candidates for such treatment, and appropriate regimens.